Inequalities in complete childhood immunisation in Nepal: results from a population-based cross-sectional study - In Han Song; Elizabeth Palley; Madhu Sudhan Atteraya (BMJ Open)
Objective To investigate the effect of different aspects of inequality on childhood immunisation rates in Nepal. The study hypothesised that social inequality factors (eg, gender of a child, age of mother, caste/ethnic affiliation, mother’s socioeconomic status, place of residence and other structural barrier factors such as living in extreme poverty and distance to health facility) affect the likelihood of children being immunised.Design Using gender of a child, age of mother, caste/ethnic affiliation, mother’s socioeconomic status, place of residence and other structural barrier factors such as living in extreme poverty and distance to health facility as independent variables, we performed bivariate and multivariate logistic regression analyses.Setting This study used data from the most recent nationally representative cross-sectional Nepal Demographic and Health Survey in 2016.Participants The analysis reviewed data from 1025 children aged 12–23 months old.Outcome measures The main outcome variable was childhood immunisation.Results Only 79.2% of children were fully immunised. The complete vaccination rate of ethnic/caste subpopulations ranged from 66.4% to 85.2%. Similarly, multivariate analysis revealed that children from the previously untouchable caste (OR 0.58; CI 0.33 to 0.99) and the Terai caste (OR 0.54; CI 0.29 to 0.99) were less likely to be fully immunised than children from the high Hindu caste.Conclusion Given Nepal’s limited resources, we suggest that programmes that target the families of children who are least likely to be fully immunised, specifically those who are not only poor but also in financial crises and ‘underprivileged’ caste families, might be an effective strategy to improve Nepal’s childhood immunisation rates.